The use of conceptual and categorical apparatus in the cross-national comparative researches - Dariya Logvinova (Історико-політичні проблеми сучасного світу, 2017)
At the beginning of the XXI century a noticeable transformation of migration processes is observed under the influence of globalization, which effect the change of social, cultural, spiritual and economic models of different countries and world regions more and more actively. This stipulates the necessity for host countries to improve migration policies for more effective control over economic, social and cultural advantages or, vice versa, disadvantages, which international migration brings with it. Consequently, the necessity of constant examination of this problem seems logical, including the level of cross-national comparative researches, during which the study of the same phenomenon in two or more countries in various socio-cultural conditions with the usage of the same tools takes place. Taking into consideration the variable and unpredictable nature of the problem, the necessity of the stable basis for such researches is transparent, first of all, the need of permanent generally accepted and used conceptual and categorical apparatus, which predetermines primary importance of the research of this apparatus in the field of migration; in this context, the analysis of using of the terms “migrant” and “ethnic minority” in the scientific political and social discourses of such countries, as Canada, Great Britain and Germany is given in the case of this article.